Apple cake - Casey, Dawn, 1975- (Frances Lincoln Children's Books, an imprint of The Quarto Group, 2019)
Join a young girl for a walk through the countryside to gather ingredients for a delicious cake: honey from the bees, milk from the cows, and apples from the trees. This simple story teaches little ones to celebrate the natural world and give thanks for nature's gifts.--